PENGARUH PEER EDUCATIOAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN HIV/AIDS - Sri Dearmaita Purba; Frida Liharris Saragih; Yunida Turisna Octavia (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
HIV/AIDS (Human Immunodeficiency Virus/Acquired Immunodeficiency Virus Syndrome) is a global problem that has hit the world, including our country, Indonesia, which has an increase in cases reported every year. The high rates of HIV/AIDS cases in North Sumatra is a serious problem that must be addressed to stop the spread of HIV/AIDS, especially among teenagers who are in the vulnerable age group with risky behavior. The purpose of this study was to analyze the level of knowledge and attitudes of teenagers towards HIV/AIDS prevention. The research method used is a quasi-experimental design with one group pre-test and post-test with a total sample of 59 people. Data analysis was performed using the Wilcoxon test. The results of this study showed that knowledge affects the treatment of counseling with a p-value of 0.000 and attitudes affect the treatment given with a p-value of 0.000. The conclusion of this study is that peer education affects the level of knowledge and attitudes of teenagers in Kelurahan Dwikora. Suggestions in this study are for teenagers to update HIV/AIDS information and active in sharing information with the surrounding environment for HIV/AIDS prevention.